Reallocations in acne healthcare: exploring the possible roles and added value of non-physicians by a mixed-methods study design - Femke de Vries; Marlies Welbie; Esther Tjin; Rieke Driessen; Peter van de Kerkhof (BMC, 2021)
Abstract Background A highly promoted opportunity for optimizing healthcare services is to expand the role of non-physician care providers by care reallocation. Reallocating care from physicians to non-physicians can play an important role in solving systemic healthcare problems such as care delays, hospital overcrowding, long waiting lists, high work pressure and expanding healthcare costs. Dermatological healthcare services, such as the acne care provision, are well suited for exploring the opportunities for care reallocation as many different types of care professionals are involved in the care process. In the Netherlands, acne care is mainly delivered by general practitioners and dermatologists. The Dutch healthcare system also recognizes non-physician care providers, among which dermal therapists and beauticians are the most common professions. However, the role and added value of non-physicians is still unclear. The present study aimed to explore the possibilities for reallocating care to non-physicians and identify drivers for and barriers to reallocation. Methods A mixed-method design was used collecting quantitative and qualitative data from representatives of the main 4 Dutch professions providing acne care: dermatologists, GP's, Dermal therapists and beauticians. Results A total of 560 questionnaires were completed and 24 semi-structured interviews were conducted. A broad spectrum of non-physician tasks and responsibilities were delineated. Interviewed physicians considered acne as a low-complexity skin condition which made them willing to explore the possibilities for reallocating. A majority of all interviewees saw a key role for non-physicians in counselling and supporting patients during treatment, which they considered an important role for increasing patients' adherence to proposed treatment regimes, contributing to successful clinical outcome. Also, the amount of time non-physicians spend on patients was experienced as driver for reallocation. Legislation and regulations, uncertainties about the extent of scientific evidence and proper protocols use within the non-physician clinical practice were experienced as barriers influencing the possibilities for reallocation. Conclusions Delineated roles and drivers demonstrate there is room and potential for reallocation between physicians and non-physicians within acne healthcare, when barriers are adequately addressed.